Rethinking the Impact of Single Continuing Educational Activities: Navigating Complexity Through Insights from Real-World Evaluation and Contemporary Literature - Robert Schaefer; Joerg Stein; Louise Niven; Mia Hill; Onno Kaagman; Anja J. Gerrits; Pan Chen; Yvonne Oliver; Eugene Pozniak; Cara L. Mcfarlane; Denise Thom; Arne Stachmann; et al. (Journal of CME)
Real-world evaluation data strongly suggest that substantial multi-level heterogeneity of continuing education (CE) audiences, though considered highly desirable, poses severe challenges to the assessment of what a single CE activity might have contributed to either improve or maintain achievements or prevent change for the worse. This relates in particular to change in higher levels of outcomes, such as performance, patient health, and/or community health. This sets narrow limits to the design of an objective, reliable and reasonably valid assessment of change in evaluating the effectiveness of a single CE activity. Although CE may be more effective in leading to consistent behaviour in homogeneous groups with regard to background and motivation, trying to reduce the various levels of heterogeneity would be an unrealistic, and also unwanted, approach. Thus, we still have to trust physicians (and other healthcare professionals) to exercise their professionalism in pursuit of individual opinion forming trajectories in the best interests of their patients. However, providers may also choose some more targeted approaches to influence the mindset even in heterogeneous learner groups:- integrating not only knowledge and competence but also current performance gaps into pre-/post-tests- increasing opportunities for discussion will allow optimal matching of the individual needs of participants with the CE content. When reported, unprecedented numbers of participants’ questions (>50 per webinar) have been processed during and/or after an e-learning activity, and even higher numbers of interactions might be expected in demand use of e-learning material. Thus, e-learning in combination with long-term faculty engagement has promising potential for sustainable competence.